Low-latency handover in a wireless ATM LAN. - Naylon, J. (IEEE Journal on selected areas in communications)
The micro- and picocellular architectures proposed for wireless ATM LANs lead to wireless terminals frequently changing their point of attachment to the network. Because ATM connections have quality of service (QoS) guarantees which must be maintained, handover must be as seamless as possible. We present a novel architecture and protocol which primarily aims to keep the interruption period due to handover low, rather than seeking to keep the process entirely lossless. We compare the tradeoffs made, with those in other schemes from the literature, and give quantitative results from an implementation of our scheme on a 10 Mbits/s-1 prototype wireless ATM LAN